Penyusunan Skedul Suhu dan Kelembaban Awal untuk Pengeringan di Dalam Tanur Pengering Konvensional bagi Kayu Durian Bersortimen 55 X 195 mm - Yustinus Suranto (Fakultas Kehutanan Universitas Gadjah Mada, 2009)
Schedule Development of Initial Temperature and Relative Humidity for Conventional Drying of Durian Wood in Dimension of 55 mm thick and 195 mm wideDecreasing supply of most commercial depterocarp wood as raw material inspirates wood working industry producing building construction component to look for uncommercial wood to be utilized. Proper utilization of these woods must be based on wood properties consisting of wood basic and processing properties. Drying property is one of the most important wood processing property. Proper drying process will be the main key to utilize effectively and ensure to get high quality wood product.Durian (Durio spp) is one of uncommercial wood grown naturally in Sulawesi island forest. This wood is used by wood industr to produce building component to be exported. There is no yet drying schedule formulation of this wood lumber in dimension of 55mm thick and 195 mm wide. The objective of this research was to develop drying schedule for durian wood in that dimension. Drying schedule was developed by the result of quick drying test. The formulation of drying schedule was elaborated based on Terazawa method.The research result showed that initial moisture content and specific gravity of this wood was 103.4% and 0.4 respectively. Theoretically, the first drying schedule was 54oC as an initial remperature and 80oC as a final temperature. Web bulb depression for the initial step of drying was 4oC and for the end step was 30oC. The range of relative himidity were 80% to 17%. These drying schedule was coded by T5F6.